The genus Macrosiphoniella (Hemiptera, Aphididae, Macrosiphini) in Spain, with description of two new species - Nafría, Juan M. Nieto; Martínez-Sáez, César; Durante, M. Pilar Mier; Stekolshchikov, Andrey V.; González, Raquel A. Mazé (Zootaxa, 2026)
The Spanish fauna of the genus Macrosiphoniella (Hemiptera, Aphididae, Macrosiphini) has been studied through (1) a complete bibliographic review and (2) the study of the specimens preserved in the aphid collection of the University of León. Twenty-four species, belonging to four subgenera, are now known in Spain. Macrosiphoniella aetnensis is removed from the Spanish aphid catalogue. The subgenus Papillomyzus, and the species M. (M.) subterranea, M. (M.) szalaymarzsoi and M. (P.) papillata are recorded for the first time in Spain. Two species are described: M. (M.) valdeorresa Mier Durante & Nieto Nafría, sp. nov. from apterous viviparous females collected on Helichrysum stoechas in Valdeorras natural region (Orense province), and M. (M.) monegrina Nieto Nafría & Mier Durante, sp. nov. from apterous and alate viviparous females collected on Artemisia herba-alba in Los Monegros natural region (Huesca and Zaragoza provinces). Additionally, data are presented on some alate viviparae collected with traps in two localities in the province of León that could belong to an unnamed species. Thirty-two first provincial records are provided, as well as nine aphid-host plant relationships not compiled in the on-line book “Blackman & Eastop’s Aphids on World’s Plants” (Favret & Aphid Taxon Community 2025).